Work and Labour as Metonymy and Metaphor - Olivier Frayssé (tripleC: Communication, Capitalism & Critique, 2014)
This paper proposes to use the tools of literary analysis (the reference to subtexts) and of linguistics (metaphor and metonymy) to shed light on the work/labour controversy and, beyond that, to map the galaxy of representations of work/labour through a study of the meanings associated with work/labour in several languages. It aims to provide a set of theoretical tools that can be used to find a common language in order to discuss digital work/labour issues as a subcategory of work/labour issues in general.